High Species Richness of Decapod Crustaceans on an Urban Rocky Shore Beach - Mikel Rodríguez-Hidalgo; Juan Lucas Cervera; Jose A. Cuesta (Diversity, 2023)
The rocky intertidal shore of La Caleta, an urban beach located in Cádiz (SW Spain), was surveyed for decapod crustaceans over a year. Samplings were taken monthly (March 2015 to February 2016) in three differentiated zones during the spring low tides of every month at five sites, differentiated according to the hydrodynamic regimes and intertidal levels. A qualitative sampling (present/absent) was carried out by visual identification (minimally invasive), and only those specimens with uncertain identification were collected by hand, studied at the laboratory, or identified using their DNA barcode. A total of 44 species were identified. Comparison with species richness of decapod crustaceans in other Atlantic and Mediterranean intertidal or subtidal ecosystems (including protected areas) shows higher values in La Caleta, a surprising fact considering the type of habitat and its placement (an urban and unprotected shore).